Comparación y Efecto del Homogenizado en Billets de Aluminio AA 6063 - Olmedo, Bladimiro Hernán Navas; Moscoso, Hernán Alberto Navas (KnE Engineering, 2018)
The lack of comparative studies about the distribution of the main alloying elements along aluminum billet´s AA 6063 widely use in extrusion companies to produce aluminum profiles, It makes necessary to counterpoise the difference between homogenized billet produced in horizontal continuous casting machine and a billet produced in vertical semi-continuous casting process. Applying spectrometric tests to quantify the weight percent of main alloying elements, brings out its own nature of each production process on every billet. Nevertheless, helped out by a metallographic test reveals in one billet the negative effect of an inadequate process of homogenization after the heat treatment process T5 in the aluminum profiles that holds it back to reach an adequate Webster hardness related to quality assurance. It reflects that is not enough to have a billet with a uniform chemical composition but the importance of an adequate billet´s heat treatment in order to be use in the extrusion process. Keywords: AA 6063, Billet, Comparison, Homogenized